PENGARUH ELECTRONIC WORD OF MOUTH, PROMOSI DAN KUALITAS PELAYANAN TERHADAP MINAT BERKUNJUNG GENERASI Z PADA DESTINASI WISATA HALAL PROVINSI JAWA BARAT - Ali Hanafiah; Mas Wahyu Wibowo; Fitria Damayanti (Universitas Mercu Buana, 2020)
This study aims to examine the visiting intention of Generation Z to West Java as a halal tourism. West Java has the potential to become the leading halal tourism in Indonesia. West Java also has a crucial role in the development of the Sharia economy, considering that 46.5 million people in this country live in this area. This province also has a wealth of attractive artistic treats, a fairly thick culture, and the potential for natural resources (geographical factors) which are considered to be the selling point as a tourist destination. There are three variables that will be tested in this study to predict the visiting intention, namely Electronic Word of Mouth, Promotion and Service Quality. The questionnaire was distributed to 170 generation Z respondents and the data were processed using SmartPLS version 3.2.9. Electronic Word of Mouth, Promotion, and Service Quality have a positive and significant impact on generation Z's interest in visiting West Java as a halal tourist destination. West Java has a destination facility that offers open space, and facilitates generation Z to take selfies with a unique background. All these facilities are provided to accommodate the needs of Muslims to carry out their prayers.